SPECIFICS OF PAID EDUCATIONAL SERVICES AS A COMMERCIAL ACTIVITY - M. Ilina; I. Chepurova; A. Gladysheva (Вестник Северо-Кавказского федерального университета)
The article deals with the problems arising in the process of organization of paid (commercial) educational services. The characteristic of educational services is presented, the main types of paid educational services are characterized. The properties of paid educational services as a subject of entrepreneurial activity are analyzed, conclusions about the effectiveness of the provision of paid services in the field of education on the example of municipal educational organizations of the city of Tambov are drawn. The article is of interest to specialists involved in the provision ofpaid educational services, for the heads of educational organizations, as well as for students studying marketing and management.